UNDERSTANDING TAX EVASION TENDENCIES: HOW MUCH DO BELIEFS MATTER? - Fransiska, Fransiska; Yohanes Mardinata Rusli (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2025)
This study aims to examine the influence of Machiavellianism, Love of Money, Materialism, and Religiosity on tax evasion tendencies by applying Attribution Theory and Social Cognitive Theory to understand the process of individual justification and agency. This quantitative study uses primary data collected through a questionnaire survey distributed to individual taxpayers (WPOP) in the Greater Jakarta area (Jabodetabek). The sampling technique applied is purposive sampling, resulting in 197 valid respondents. Data were analyzed using multiple linear regression with the help of SPSS. The results show that Machiavellianism and Love of Money have a positive and significant effect on tax evasion tendencies. Materialism has a negative and significant effect, while religiosity shows a positive and significant impact. These findings indicate that a combination of personality traits, financial motivation, and individual ideological perceptions influences tax evasion behavior. The practical implication of this research can serve as a reference for tax authorities in formulating more effective educational and supervisory strategies by considering taxpayers' psychological factors.